A case report of metastatic lung adenocarcinoma with long-term survival for over 11 years - Matsuzaki, Tatsu (Medicine (Baltimore), 2019)
RATIONALE: This is the first known report in the English literature to describe a case of metastatic non-small cell lung cancer that has been controlled for >11 years. PATIENT CONCERNS: A 71-year-old man visited our hospital because of dry cough. DIAGNOSIS: Chest computed tomography revealed a tumor on the left lower lobe with pleural effusion, and thoracic puncture cytology indicated lung adenocarcinoma. INTERVENTIONS: Four cycles of carboplatin and docetaxel chemotherapy reduced the size of the tumor; however, it increased in size after 8 months, and re-challenge chemotherapy (RC) with the same drugs was performed. Repeated RC controlled disease activity for 6 years. After the patient failed to respond to RC, erlotinib was administered for 3 years while repeating a treatment holiday to reduce side effects. The disease progressed, and epidermal growth factor receptor (EGFR) gene mutation analysis of cells from the pleural effusion detected the T790 M mutation. Therefore, osimertinib was administered, which has been effective for >1 year. OUTCOMES: The patient has survived for >11 years since the diagnosis of lung cancer. LESSONS: Long-term survival may be implemented by actively repeating cytotoxic chemotherapy and EGFR-tyrosine kinase inhibitor administration.